Raising the Intrinsic Safety of Layered Oxide Cathodes by Surface Re‐Lithiation with LLZTO Garnet‐Type Solid Electrolytes. Issue 19 (9th April 2022) - Wang, Junyang; Chen, Rusong; Yang, Lufeng; Zan, Mingwei; Chen, Penghao; Li, Yu; Li, Wenjun; Yu, Huigen; Yu, Xiqian; Huang, Xuejie; Chen, Liquan; Li, Hong
Abstract: Battery safety concerns are becoming more and more prominent with the increasing demands of lithium‐ion batteries (LIBs) with higher energy density. The greatest threat to battery safety derives from the easy release of oxygen from the high‐capacity layered oxide cathodes at highly delithiated states and subsequent exothermic reactions with reductive agents in batteries. Herein, it is demonstrated that solid electrolyte Li6.5 La3 Zr1.5 Ta0.5 O12 (LLZTO) can supply lithium ions to re‐lithiate the charged LiCoO2 at elevated temperatures. Such a re‐lithiation process can lower the state‐of‐charge of LiCoO2, and thus, inherently postpones its structural decomposition and the associated release of oxygen during the heating process. The LiCoO2 /graphite full cell with 1 wt% addition of LLZTO demonstrates remarkably enhanced safety performances. This work proposes a strategy that through the adoption of solid electrolytes to solve safety issues raised from both flammable liquid electrolytes and high capacity cathodes, to achieve intrinsically safe LIBs or solid‐state batteries. Abstract : Garnet‐type solid electrolyte LLZTO supplies lithium ions to retard the oxygen release of oxide cathode during heating. LLZTO acts bifunctionally to solve the safety issues from flammable liquid electrolytes and high‐capacity layered cathodes at high SOC. Consequently, LiCoO2 /graphite cell with 1 wt% LLZTO addition achieves significantly enhanced safety performances.